Ultrafast Non‐Equilibrium Synthesis of Cathode Materials for Li‐Ion Batteries - Zhu, Wei; Zhang, Jingchao; Luo, Jiawei; Zeng, Cuihua; Su, Hai; Zhang, Jinfeng; Liu, Rui; Hu, Enyuan; Liu, Yuansheng; Liu, Wei‐Di; Chen, Yanan; Hu, Wenbin; et al. (Advanced materials (Weinheim), 2023)
The synthesis of cathode materials plays an important role in determining the production efficiency, cost, and performance of lithium‐ion batteries. However, conventional synthesis methods always experience a slow heating rate and involve a complicated multistep reaction process and sluggish reaction dynamics, leading to high energy and long time consumption. Herein, a high‐temperature shock (HTS) strategy is reported for the ultrafast synthesis of cathode materials in seconds. The HTS process experiences an ultrahigh heating rate, leading to a non‐equilibrium reaction and fast reaction kinetics, and avoids high energy and long time consumption. Mainstream cathode materials (such as LiMn2O4, LiCoO2, LiFePO4, and Li‐rich layered oxide/NiO heterostructured material) are successfully synthesized with pure phases, oxygen vacancies, ultrasmall particle sizes, and good electrochemical performance. The HTS process not only provides an efficient synthesis approach for cathode materials, but also can be extended beyond lithium‐ion batteries. An ultrafast high‐temperature shock strategy is proposed to synthesize cathode materials in seconds for lithium‐ion batteries, avoiding high energy and long time consumption. It provides an ultrahigh heating rate, leading to a non‐equilibrium reaction and fast reaction kinetics. Mainstream cathode materials are successfully synthesized with pure phases, oxygen vacancies, ultrasmall particle sizes, and good electrochemical performance, indicative of a universal and efficient synthesis approach.